Obtaining and Characterization of Hybridomas Producing Monoclonal Antibodies against Coronavirus SARS-CоV-2 - G. V. Kuklina; S. S. Ipatov; A. S. Gorshkov; D. V. Pechenkin; A. V. Eremkin; A. V. Kuznetsovsky; A. S. Tumanov; I. V. Darmov (Проблемы особо опасных инфекций, 2023)
The aim of the work was to obtain and characterize hybridomas producing monoclonal antibodies to antigens of coronavirus SARS‑CoV‑2, promising for the construction of diagnostic immunochemical tests. Materials and methods. Recombinant nucleocapsid and receptor binding fragment of spike protein of SARS‑CoV‑2 were used for immunization of BALB/c mice. Antigens were absorbed on aluminium hydroxide gel and injected subcutaneously to BALB/c mice at a 7-day-interval. Immune splenocytes and myeloma cells SP2/0-Ag14 were fused by polyethylene glycol 1450. Cell cultures producing specific antibodies against nucleocapsid and receptor binding fragment were selected applying indirect ELISA in 96-well plates sensitized by desired antigens. Clones of hybridomas were obtained using the method of limiting dilutions. Production properties were studied through in vitro cultivation in 24-well culture plates. Immune-ascitic fluids were collected during the cultivation of hybrid cells in peritoneal cavities of BALB/c mice. Monoclonal antibodies were purified by affinity chromatography on protein A sepharose sorbent, conjugated with horseradish peroxidase, and tested for the possibility to be used in sandwich ELISA for detection of inactivated SARS‑CoV‑2 coronavirus strain “Isolate B”. Results and discussion. As a result of hybridization and selection of clones, hybridomas producing monoclonal antibodies to nucleocapsid and receptor binding fragment of SARS‑CoV‑2 have been obtained. During the in vitro and in vivo cultivation the clones maintained the consistent proliferative and antibody producing activity. The application of monoclonal antibody 415D12 as a capture one and 411D12 antibody conjugated with horseradish peroxidase as a detector antibody in ELISA allows for identifying SARS‑CoV‑2 coronavirus at a minimum concentration of 1·103 PFU per ml.